Membrane Fouling alleviation in pressure-retarded osmosis process for osmotic power generation - Sigurður John Einarsson 1996- (2021)
Climate change is an existential threat to the global environments and humanities existence. In order to achieve carbon neutrality to prevent the global mean temperature rising above 1.5℃, sustainable energies must be developed to phase out the reliance on CO2 emitting fossil fuel energies. Pressure-retarded osmosis (PRO) has shown the technical ability to capture renewable energy from a salinity gradient between two streams through a semipermeable membrane. Recently, thermal associated PRO has been given great attention due to its enhanced power generation. In Iceland, the unique local natural resources allow for the employment of pristine freshwater as a feed solution and high temperature geothermal waste brine or waste gas as a draw solution for energy production. However, PRO membrane fouling is a major challenge that can influence the energy production. In this study, the effects of physical fouling remediation methods (e.g. clean water flushing, osmotic back washing, air sparging, and chemical cleaning) on PRO performance have been examined by using a synthetic solution (simulating an alkali solution for capturing geothermal gases) and real geothermal brine. The results found that intermittent introduction of air sparging best prolonged high membrane performance. The technical feasibility and economic benefits were estimated based on experimental results to illustrate the possible future implementation of PRO in Iceland. In the ideal scenario using the highest average measured fluxes for geothermal brine and NaHCO3 solution (9 and 30.4 LMH respectively) a full scale plant could project over $3.5 million. Landsvirkjun - Partial funding and geothermal water Orka Náttúrunnar - Geothermal Water